Abstinence from Masturbation and Hypersexuality. - Zimmer, Felix; Imhoff, Roland (Archives of Sexual Behavior, 2020)
Despite the lack of evidence for negative health effects of masturbation, abstinence from masturbation is frequently recommended as a strategy to improve one's sexual self-regulation. We adopted a framework of perceived problems with pornography to collect first hints about whether abstinence from masturbation stems from a psychological and behavioral "addiction" or conflicting attitudes. In an online questionnaire survey recruited via a non-thematic Reddit thread (n = 1063), most participants reported that they had tried to be abstinent from masturbation. As visible from zero-order correlations and multiple linear regression, motivation for abstinence was mostly associated with attitudinal correlates, specifically the perception of masturbation as unhealthy. While there were associations with hypersexuality, no significant correlation with behavioral markers such as maximum number of orgasms was found. Higher abstinence motivation was related to a higher perceived impact of masturbation, conservatism, and religiosity and to lower trust in science. We argue that research on abstinence from masturbation can enrich the understanding of whether and how average frequencies of healthy behavior are pathologized.